An empirical study on the potential of word embedding techniques in bug report management tasks - Chen, Bingting; Zou, Weiqin; Cai, Biyu; Meng, Qianshuang; Liu, Wenjie; Li, Piji; Chen, Lin (Empirical software engineering : an international journal, 2024)
Context Representing the textual semantics of bug reports is a key component of bug report management (BRM) techniques. Existing studies mainly use classical information retrieval-based (IR-based) approaches, such as the vector space model (VSM) to do semantic extraction. Little attention is paid to exploring whether word embedding (WE) models from the natural language process could help BRM tasks. Objective To have a general view of the potential of word embedding models in representing the semantics of bug reports and attempt to provide some actionable guidelines in using semantic retrieval models for BRM tasks. Method We studied the efficacy of five widely recognized WE models for six BRM tasks on 20 widely-used products from the Eclipse and Mozilla foundations. Specifically, we first explored the suitable machine learning techniques under the use of WE models and the suitable WE model for BRM tasks. Then we studied whether WE models performed better than classical VSM. Last, we investigated whether WE models fine-tuned with bug reports outperformed general pre-trained WE models. Key Results The Random Forest (RF) classifier outperformed other typical classifiers under the use of different WE models in semantic extraction.We rarely observed statistically significant performance differences among five WE models in five BRM classification tasks, but we found that small-dimensional WE models performed better than larger ones in the duplicate bug report detection task. Among three BRM tasks (i.e., bug severity prediction, reopened bug prediction, and duplicate bug report detection) that showed statistically significant performance differences, VSM outperformed the studied WE models. We did not find performance improvement after we fine-tuned general pre-trained BERT with bug report data. Conclusion Performance improvements of using pre-trained WE models were not observed in studied BRM tasks. The combination of RF and traditional VSM was found to achieve the best performance in various BRM tasks.